In-silico prediction of potential inhibitors against phosphatidylinositol 3-kinase catalytic subunit alpha involved in head and neck squamous cell carcinomas. Issue 10 (21st June 2022) - Madhukar, Geet; Subbarao, Naidu
Abstract: Head and neck squamous cell carcinoma (HNSCC) is one of the most common cancers, globally. Its high mortality rates remained unaltered in the last three decades, therefore, there is an enormous need for novel therapeutics. The most frequent somatically mutated oncogenic pathway in HNSCC tumors is the Phosphatidylinositol-3-kinases (PI3K) pathway. PI3Ks are lipid kinases involved in the regulation of cell survival, growth and metabolism. PI3Ks phosphorylates PI (4, 5) P2 (PIP2) converting it to PI (3, 4, 5) P3 (PIP3). Alterations such as mutation, gene amplification and overexpression in PIK3CA, encoding the catalytic subunit p110α of PI3K pathway were found to be prevalent. The aberrant activation leads to irregulated cell growth due to improper p110α enzymatic activity. p110α is therefore, considered a potential oncogenic target for cancer therapy. The only FDA approved specific inhibitor of p110α is Alpelisib (BYL719). Therefore, designing more effective and specific p110α inhibitors could be a promising strategy in the treatment of HNSCC. The present study aims to find out the potent and novel inhibitors of p110α using High Throughput Screening (HTS) of huge databases (National Cancer Institute (NCI), Life Chemicals, ChemDiv and ChEMBL) and Molecular Dynamic Simulations. As a result, from more than 400, 000 compounds, a total of 3 best candidate compounds (Echinacoside, Isoacteoside, K284-4402) were selected and validated for their binding to catalytic site of p110α and stability during Molecular Dynamics (MD) simulations. The binding free energy (calculated from MM-PBSA) of the selected compounds, Echinacoside, Isoacteoside, K284-4402 were −23.43 kcal/mol, −33.02 kcal/mol and −30.57 kcal/mol, respectively, which suggested these compounds bind to p110α with higher affinity than Alpelisib which has binding free energy −20.9 kcal/mol. This study provides a significant in-depth understanding of p110α inhibitors that can be used in the development of potential therapeutics against HNSCC. Communicated by Ramaswamy H. Sarma